PENGARUH WAKTU PEMANASAN PADA PEMBUATAN BIODIESEL DARI LIMBAH JEROAN IKAN MENGGUNAKAN MICROWAVE - Shintawati Dyah Purwaningrum; Sukaryo Sukaryo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
Biodiesel is an alternative energy that can replace petroleum-based diesel oil. The biodiesel production uses raw material for fish offal waste with microwave radiation and the addition of KOH as a catalyst. The process of esterification and transesterification is carried out in a three-neck flask that has been connected to a microwave and condenser. This study uses variables in the form of micro-wave power 300, 450, 600 and 800 watts, the ratio of reaction time 20, 40, 50, and 60 minutes with mole ratio of oil with 1:18 methanol, and  KOH catalyst. The biggest yield  produced in the biodiesel production process with micro radiation at a heating time of 40 minutes, microwave power of 600 watts, the ratio 1:18 was 97% and the lowest yield was at 20 minutes heating time, microwave power 300 watts, the ratio of fish offal oil reactants with methanol 1:18 is 82%. Biodiesel with the highest yield was analyzed by GCMS to determine the FAME content formed and biodiesel characteristic test. Biodiesel in this study has met the biodiesel requirements of the Indonesian National Standard. Keywords:  fish  offal  waste,  microwave,  time  variation,  biodiesel,  biodiesel qualit